Efektivitas Pengamanan Intelijen Kepolisian Negara Republik Indonesia dalam Eksekusi Obyek Sengketa Studi di Wilayah Hukum Polsek Batahan Polres Mandailing Natal Polda Sumatera Utara - Helmi Jufri; Arifin Tumuhulawa; Ramdhan Kasim (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
This article aims to determine and analyze the effectiveness of the security of the Indonesian National Police Intelligence in the execution of disputed objects. Study in the Legal Area of the Batahan Police, Mandailing Natal Police (Madina), North Sumatra Police and to determine and analyze the factors that influence the security of police intelligence at the Batahan Police, Polda. North Sumatra regarding the execution of disputed objects. This type of research uses a Sociological Juridical Approach, namely a sociological juridical approach which is based on applicable statutory provisions linked to legal theory and looks at the reality that occurs in society by studying the law and reality in the field. The effectiveness of security at the Mandailing Natal (Madina) Police Department of North Sumatra Police regarding the execution process for disputed objects in North Sumatra Province based on Perkap BIN No. 2 of 2013. The implementation of security carried out by police personnel regarding the land dispute execution process based on obtaining data from all indicators based on security aspects of the North Sumatra Regional Police's Ditintelkam and Banlahan Police showed less effective results. On the other hand, the police have a role as law enforcers, so they must try to mediate in every conflict that occurs in society, especially in efforts to handle land execution cases. In an effort to increase the effectiveness of the police in securing land executions, they must adhere firmly to the law so as not to violate the role and function of the police, namely as protectors of the community, sometimes they are negligent and violate provisions.